Розробка компонентів системи для обміну повідомленнями в режимі реального часу з використанням технологій хмарних сервісів - Гробовий, Д. В. (ХНУРЕ, 2024)
In today's digital world, the ability to communicate instantly is not just a convenience but a necessity for both personal connections and business operations. Developing an application for real-time messaging using cloud services is at the forefront of meeting this need. The integration of cloud technology ensures that this kind of app can offer scalable, reliable messaging solutions that are accessible from anywhere, at any time. This initiative addresses the essential demand for immediate communication while leveraging the power and flexibility of the cloud. By focusing on the technical and practical aspects of cloud-based messaging, developers can create a platform that facilitates seamless, secure exchanges of information. This approach not only simplifies communication but also introduces a level of efficiency and connectivity that is vital in our fast-paced digital age. The journey of developing such an application involves navigating through various challenges, from ensuring data security to providing a user-friendly interface. Yet, the potential to enhance how we communicate makes this venture a compelling and worthwhile pursuit.
Keywords: обмін повідомленнями; хмарний сервіс